1991
DOI: 10.1063/1.349059
|View full text |Cite
|
Sign up to set email alerts
|

Artificial dielectric properties of microscopic metallized filaments in composites

Abstract: Measurements have been made of the dielectric response of distributions of metallized fibers aligned in epoxy matrices for different loading fractions and fiber lengths. These have been shown to be in reasonable agreement with a simple independent particle theory. Use of the theory allows classification of fiber dielectric behavior by fiber conductivity and a characteristic length. Some aggregation of the fibers has been observed, even at relatively low loading densities. Computer simulation suggests enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The results clearly demonstrated that the high aspect ratios of the metal cylinders led to high dielectric constants that were extremely anisotropic. Stockton et al (48) conducted further investigations over a wider range of concentrations and tubule lengths and also studied conventional fibers. Their results were in substantial agreement with those of Behroozi et al They demonstrated that the small diameter (~0 .…”
Section: Ternplating Concepts: Metallization For Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The results clearly demonstrated that the high aspect ratios of the metal cylinders led to high dielectric constants that were extremely anisotropic. Stockton et al (48) conducted further investigations over a wider range of concentrations and tubule lengths and also studied conventional fibers. Their results were in substantial agreement with those of Behroozi et al They demonstrated that the small diameter (~0 .…”
Section: Ternplating Concepts: Metallization For Applicationsmentioning
confidence: 98%
“…Metal-clad tubules could be one possible route to the fabrication of such composites. Stockton et al (48) and Behroozi et al (49) have fabricated and . This composite was then cast into rods and sheets.…”
Section: Ternplating Concepts: Metallization For Applicationsmentioning
confidence: 98%
“…Originally, these composites were designed to avoid percolation by minimizing contact between tubules. [10][11][12] The purpose was to produce artificial dielectrics with large real permittivities and low loss. By using magnetic orientation of ferromagnetically coated rods, random orientational contact between conductors was suppressed.…”
Section: Sample Fabricationmentioning
confidence: 99%
“…Studies have shown that particle conductivity has a great effect on the imaginary permittivity. 18 In general, the as-plated metal in electroless deposition has a lower conductivity than its bulk. 19 When the composite annealed at 400 C, Ni nanoparticles become complete crystallization, and they are in contact with each other due to their higher content in 80 wt% coaxial sample.…”
Section: Effects Of Different Weight Percentages On the Composite Permentioning
confidence: 99%